Primary synovial osteochondromatosis of the shoulder: a rare cause of shoulder pain. Issue 1 (28th November 2018) - Poyser, Emma; Morris, Rhys; Mehta, Hemang
Abstract : Synovial osteochondromatosis is a benign neoplastic condition which manifests as multiple cartilaginous or osteocartilaginous nodules within a joint, bursa and tendon sheath. It typically results in pain and stiffness of the affected joint, and is thought to arise as a result of synovial membrane proliferation and metaplasia. 1 We report the diagnosis and management of a 36-year-old man who presented with a long history of shoulder pain, which had been managed conservatively prior to referral to orthopaedics. Following investigation and subsequent diagnosis, he underwent successful surgical treatment of primary synovial osteochondromatosis, in the form of open synovial debridement and excision of nodules, with no recurrence demonstrated at 1-year follow-up. This case illustrates the diagnosis and management of primary synovial osteochondromatosis, and emphasises the importance of serial imaging and specialist referral for cases of diagnostic uncertainty or failure to respond to treatment as expected.